Case Report: Improved Choroidal Circulation in a Patient with Unilateral Acute Idiopathic Maculopathy. Issue 9 (2nd September 2022) - Sotozono, Akiko; Mizobuchi, Kei; Hayashi, Takaaki; Shikauchi, Mamiko; Nakano, Tadashi
Abstract : SIGNIFICANCE: Unilateral acute idiopathic maculopathy is a rare retinochoroidal disorder, the cause of which is unknown. Multimodal retinal imaging obtained in this case suggests that the cause of unilateral acute idiopathic maculopathy is impaired choroidal circulation. PURPOSE: This study aimed to report a patient with unilateral acute idiopathic maculopathy who showed improvement of choroidal circulation over time in optical coherence tomography angiography images. CASE REPORT: A 33-year-old woman with a prodromal flu-like illness noticed a sudden central visual field abnormality in the right eye. Five days after the onset, best-corrected visual acuity was 0.15 in the right eye. Fundus photography showed a yellowish lesion at the macula in the right eye. Optical coherence tomography showed a blurred ellipsoid zone and a thickened retinal pigment epithelium at the fovea and a disrupted/blurred ellipsoid zone and retinal pigment epithelium at the parafovea. Optical coherence tomography angiography segmentation of the choriocapillaris revealed a hypointense region at the fovea with a hyperintense region surrounding it. One week after the onset, best-corrected visual acuity was improved from 0.15 to 2.0 in the right eye. Furthermore, the yellowish macula lesion shrank, and the outer retinal layers showed improvement in optical coherence tomography. Optical coherence tomography angiography showed reduction of the hypointense region and enlargement of the hyperintense region. Approximately 1 year after the onset, the yellowish lesion was faded. Optical coherence tomography revealed an almost normal ellipsoid zone but a thickened interdigitation zone. Optical coherence tomography angiography also revealed an apparent hyperintense instead of the hypointense region and increased choroidal blood flow. CONCLUSIONS: The current patient showed a gradual recovery of choroidal circulation and outer retinal layer morphology 1 year after the onset of unilateral acute idiopathic maculopathy. Optical coherence tomography angiography findings indicated that the primary cause of unilateral acute idiopathic maculopathy was impaired choroidal circulation, and choroidal vessels improved morphologically over the disease course.